Stereochemistry of an Agonist Determines Coupling Preference of β(2)-Adrenoceptor to Different G Proteins in Cardiomyocytes - Woo, Anthony Yiu-Ho (American Society for Pharmacology and Experimental Therapeutics, 2009)
A fundamental question regarding receptor-G protein interaction is whether different agonists can lead a receptor to different intracellular signaling pathways. Our previous studies have demonstrated that although most β(2)-adrenoceptor agonists activate both G(s) and G(i) proteins, fenoterol, a full agonist of β(2)-adrenoceptor, selectively activates G(s) protein. Fenoterol contains two chiral centers and may exist as four stereoisomers. We have synthesized a series of stereoisomers of fenoterol and its derivatives and characterized their receptor binding and pharmacological properties. We tested the hypothesis that the stereochemistry of an agonist determines selectivity of receptor coupling to different G protein(s). We found that the R,R isomers of fenoterol and methoxyfenoterol exhibited more potent effects to increase cardiomyocyte contraction than their S,R isomers. It is noteworthy that although (R,R)-fenoterol and (R,R)-methoxyfenoterol preferentially activate G(s) signaling, their S,R isomers were able to activate both G(s) and G(i) proteins as evidenced by the robust pertussis toxin sensitivities of their effects on cardiomyocyte contraction and on phosphorylation of extracellular signal-regulated kinase 1/2. The differential G protein selectivities of the fenoterol stereoisomers were further confirmed by photoaffinity labeling studies on G(s),G(i2), and G(i3) proteins. The inefficient G(i) signaling with the R,R isomers is not caused by the inability of the R,R isomers to trigger the protein kinase A (PKA)-mediated phosphorylation of the β(2)-adrenoceptor, because the R,R isomers also markedly increased phosphorylation of the receptor at serine 262 by PKA. We conclude that in addition to receptor subtype and phosphorylation status, the stereochemistry of a given agonist plays an important role in determining receptor-G protein selectivity and downstream signaling events.